A Comparison of Two Invagination Techniques for Pancreatojejunostomy after Pancreatoduodenectomy - Katarzyna Kusnierz; Slawomir Mrowiec; Pawel Lampe (Gastroenterology Research and Practice)
Background. The aim of the study was to compare two invagination techniques for pancreatojejunostomy after pancreatoduodenectomy. Methods. For effective prevention of the development of pancreatic leakage, we modified invagination technique that we term the “serous touch.” We analysed the diameter of the main pancreatic duct, the texture of the remnant pancreas, the method of the reconstruction, pancreatic external drainage, anastomotic procedure time, histopathological examination, and postoperative complications. Results. Fifty-two patients underwent pancreatoduodenectomy with pancreatojejunostomy using “serous touch” technique (ST group) and 52 classic pancreatojejunostomy (C group). In the ST group one patient (1.9%) was diagnosed as grade B pancreatic fistula, and no patient experienced fistula grade A or C. In the C group 6 patients (11.5%) were diagnosed as fistula grade A, 1 (1.9%) patient as fistula grade B, and 1 (1.9%) patient as fistula grade C. There was a significant statistical difference in incidents of pancreatic fistula (P<0.05) and no statistical difference in other postoperative complications or mortality in comparison group. Anastomosis time was statistically shorter in the ST group. Conclusions. “Serous touch” technique appeared to be easy, safe, associated with fewer incidences of pancreatic fistulas, and less time consuming in comparison with classical pancreatojejunostomy.